A ação comunicativa na formação de professores da modalidade educação a distância (EaD) - Foletto, Denize da Silveira (2010)
This work results of a theoretical-empirical research and its purpose, following the postulation of the Theory of Communicative Action by Jürgen Habermas, to identify, to interpret and to understand the rationality that permeates the teacher s graduate in pedagogy courses in distance learning, this work also pretend to present arguments for construction of another rationality toward a new pedagogic identity centered on a communicative reason. At a first moment we object to situate and to argument this research problem showing a small notion of rationality and developing some principles to changing the rationality on the courses in distance learning. Secondly with the hermeneutics support as a meaning and a methodological approach, we search to understand the interactivity and dynamic links between Philosophy and Pedagogy. In a sequence, we made a brief historical overview of the policies of teacher training in distance education approaching the history of the distance education, the educational reform of 1990, and a study of the legislation that support this mode of education. Following, a result of this study we broach the training of teachers in Distance Education demonstrating how and why it is necessary to rethink the ways of Distance Education. The analysis shows that the Pedagogy courses on distance on two institutions researches and analyzed under the two standards of rationality - the paradigm of modern subjectivity and the paradigm of communicative reason - although they adopt a critical about the assumptions of modernity still supported by their assumptions. When we finished the searching, our challenge was to take a look at prospective, indicating the reasons for a possible (re)statement of Pedagogy in Distance; a Distance a Pedagogy that inspired by the philosophy of intersubjectivity and with the exercise argumentative of language in communicative rationality and procedural form, seek for unity in the multiplicity of voices and promotes the dialogue of knowledge.